Rare Case of Mediastinal Myeloid Sarcoma - Devi, Kanta; Adil, Salman Naseem; Ali, Natasha; Ali, Nasir; Khan, Hammad (Asian Pacific Journal of Cancer Care, 2021)
Myeloid sarcoma is a rare tumor mass with extra medullary growth pattern, composed of myeloblast or immature myeloid cells. Myeloid sarcoma (MS) is a distinct clinical presentation of acute myeloid leukemia (AML) where less than 1% of patients present with prominent extra medullary disease which most commonly involves the bone, skin, lymph node, soft tissues, gastrointestinal tract or testes. The recommended treatment regimen in isolated myeloid sarcoma or with bone marrow involvement is upfront systemic chemotherapy. We report a case of a young female with anterior mediastinal mass diagnosed as myeloid sarcoma which was refractory to chemotherapy.